Translation Shift On Noun And Noun Phrase In Frozen Movie And Subtitling - Baity, Sa'idah; , Dr. Dwi Haryanti, M.Hum; , Dra. Malikatul Laila, M. Hum (2014)
This research aims to identify the translation shift of noun and noun phrase and to describe the equivalent translation found in Frozen movie. The data in this research are English and Indonesian Frozen movie subtitling. The data source is in Frozen movie subtitle containing noun and noun phrase. The type of this research is descriptive qualitative research. The writer used observation and documentation method to collect the data. The steps were as follows; the writer watched the original film and read the movie script of Frozen movie repeatedly. After that the writer underlined the English sentence containing noun and noun phrase the subtitling of Frozen movie then wrote down them into paper. The last the writer coded the data by retyping both source and target language. The results of this research show that first, there were six types of translation shift of noun and noun phrase, i.e. From 200 data, there are 21 data or 10.5% belong to level shift of noun, 2 data or 1% belong to class shift of noun, 11 data or 5.5% belong to intra-system shift of noun, 102 data or 51% belong to level shift of noun phrase, 54 data or 27% belong to structure shift of noun phrase, and 10 data or 5% belong to intra-system shift of noun phrase. Second, there were 185 data or 92.5% belong to equivalent translation and 15 data or 7.5% belong to non equivalent translation. It means that the dominant of translation shift on noun and noun phrase in Frozen movie subtitling is level shift of noun phrase.